ON THE PROBLEM OF QUANTITATIVE MODELING FOR EVOLUTION OF ORE-MAGMATIC SYSTEMS - Sharapov V.N.; Sotnikov V.I. (My University, 1997)
Quantitative models for dynamics of the evolution of ore-magmatic systems have been developed quite irregularly. The most advanced approach is the mathematical modeling of heat and mass transfer processes for the case of origin of granitoid plutons, where magma crystallization is accompanied by retrograde boiling and development of an orthomagmatic fluid system. The least formalized description is given to the dynamics of the development of fluid ore-magmatic systems of deep fault zones and slowly spreading mid-oceanic ridges. Quantitative description of separate fragments of the evolution of a magmatic or a fluid ore-magmatic system is proposed for the ore-magmatic systems connected with shallow-depth magmatic chambers of rapidly spreading ridges and basite melts differentiating in intrusive chambers. There is no self-consistent quantitative model for the development of this kind of ore-magmatic systems yet. A similar situation exists for the case of evolution of ore-magmatic systems, appearing when basite magmas intrude the carbonate-halogen deposits of the Siberian Platform cover. Mathematical modeling for the evolution of different fluid ore-magmatic systems has several similar genetical problems solved now partly or poorly: 1) understanding of physical and physicochemical processes connected with retrograde boiling (distillation) of magma; 2) description of the process of mixing of magmatic gases and porous solutions of the rocks hosting the magmatic body; 3) description of the process of filtration of mantle-derived fluids through permeability zones of deep-seated faults. To solve these problems seems presently to be the most urgent for advancing the theory of the evolution of ore-magmatic systems.